2018
DOI: 10.14527/pegegog.2018.019
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of process of teaching function concept in an Adidactic learning environment

Abstract: This study investigates the learning of the concept of functions in an adidactic learning environment, explains the five phases of the adidactic learning environments defined in the Didactic Situation Theory and their interactions with the milieu generated within the given problem state of the students. It was carried out with 33 ninth grade students from an Anatolian high school in Balıkesir. This qualitative study was designed as a case study. Descriptive analysis was used to analyze the data from students’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…In this study, it was found that PEMTs developed more than one solution in most of the assigned tasks. It is stated in the literature that students are not willing to find more than one solution to the problem situation designed within the framework of TDS (Erümit, Arslan and Erümit, 2012;Dikkartin Övez, & Akar, 2018). This study is different from other studies in terms of developing more than one solution by PEMTs regarding a problem situation.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study, it was found that PEMTs developed more than one solution in most of the assigned tasks. It is stated in the literature that students are not willing to find more than one solution to the problem situation designed within the framework of TDS (Erümit, Arslan and Erümit, 2012;Dikkartin Övez, & Akar, 2018). This study is different from other studies in terms of developing more than one solution by PEMTs regarding a problem situation.…”
Section: Discussionmentioning
confidence: 80%
“…Bu çalışmada öğretmen adaylarına verilen görevlerin çoğunda birden fazla çözüm ürettikleri belirlenmiştir. Literatürde öğrencilerin DDT çerçevesinde tasarlanan problem durumuna birden fazla çözüm bulmakta istekli olmadıkları belirtilmektedir (Erümit, Arslan ve Erümit, 2012;Dikkartin Övez, & Akar, 2018). Bu çalışma problem durumuna ilişkin birden fazla çözüm yolu geliştirilmesi açısından diğer çalışmalardan ayrılmaktadır.…”
Section: Turkish Studies -Educational Sciencesunclassified
See 1 more Smart Citation